2008
DOI: 10.4049/jimmunol.180.2.998
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of the Jak1 FERM and Kinase Domains in Cytokine Receptor Binding and in Stimulation-Dependent Jak Activation

Abstract: Jak1 is a tyrosine kinase that noncovalently forms tight complexes with a variety of cytokine receptors and is critically involved in signal transduction via cytokines. Jaks are predicted to have a 4.1, ezrin, radixin, moesin (FERM) domain at their N terminus. FERM domains are composed of three structurally unrelated subdomains (F1, F2, and F3) which are in close contact to one another and form the clover-shaped FERM domain. We generated a model structure of the Jak1 FERM domain, based on solved FERM structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 42 publications
(64 reference statements)
1
46
0
Order By: Relevance
“…Studies of IFN-g signaling were performed on cells overexpressing Jak1 or Jak2 lysine mutants and concluded on a hierarchical activation as well, with Jak2 playing the initiator role (36). The question was recently re-examined for IFN-g with the same mutants expressed at near-endogenous levels, and the data pointed, instead, to Jak1 as the initiator (37). These studies emphasized the impact of Jak expression level and indicated a certain degree of catalytic hierarchy between two juxtaposed Jaks.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of IFN-g signaling were performed on cells overexpressing Jak1 or Jak2 lysine mutants and concluded on a hierarchical activation as well, with Jak2 playing the initiator role (36). The question was recently re-examined for IFN-g with the same mutants expressed at near-endogenous levels, and the data pointed, instead, to Jak1 as the initiator (37). These studies emphasized the impact of Jak expression level and indicated a certain degree of catalytic hierarchy between two juxtaposed Jaks.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that for receptor-unbound JAK2, the FERM domain may fold back on the JH1 and JH2 domains to provide an additional physical constraint to activation (45). The JAK1 FERM domain is involved in autoinhibition as well (59).…”
Section: Activation Of the Jaksmentioning
confidence: 99%
“…This possibility leads to the question of what distinguishes IL-27 receptor-␣ from other single chain receptors. It is conceivable that the specific interaction between a receptor scaffold and the FERM domain of a cognate Jak ultimately determines the degree of flexibility of the kinase domains and the degree of substrate accessibility (31,32).…”
Section: Volume 283 • Number 27 • July 4 2008mentioning
confidence: 99%